PENGARUH KURS, CADANGAN DEVISA DAN PRODUKSI TERHADAP EKSPOR KARET ALAM DI INDONESIA - Ananda, Santi Sri; Syafira, Syarifah; Sari, Cut Putri Melita; Rahmah, Mutia (Jurnal Ekonomi Pertanian Unimal, 2024)
This study aims to determine the influence of exchange rates, foreign exchange reserves, and production on natural rubber exports in Indonesia. The data used is secondary data in the form of a time series from 1971-2021 obtained from the World Bank and FAO (Food and Agriculture Organization). Previous findings have examined exchange rates, foreign exchange reserves, production, and general exports using different commodities. At the same time, this study specializes in exchange rates, foreign exchange reserves, and production associated with natural rubber exports in Indonesia. Data analysis uses the Vector Error Correction Model (VECM) approach, with all variables being stationary at the same level, i.e., differentiated in the first derivative. All variables must be co-integrated and have a negative ECT (Error Correction Term) value to make the model valid and usable. The results show that the exchange rate variable has a positive and insignificant effect in the short term. In contrast, in the long term, the exchange rate variable positively and significantly impacts natural rubber exports in Indonesia. The foreign exchange reserve variable positively and substantially affects natural rubber exports in Indonesia in the short term. In the long term, the foreign exchange reserve variable positively affects not significantly. Furthermore, production variables in the short term are insignificant, and in the long term, production variables have a positive but insignificant impact on natural rubber exports in Indonesia